Environmental DNA (eDNA) metabarcoding: Diversity study around the Pondok Dadap fish landing station, Malang, Indonesia - Sapto Andriyono; MD. JOBAIDUL ALAM; HYUN-WOO KIM (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Andriyono S, Jobaidul Alam Md, Kim HW. 2019. Environmental DNA (eDNA) metabarcoding: Diversity study around the Pondok Dadap fish landing station, Malang, Indonesia. Biodiversitas 20: 3772-3781. Molecular identification of species is now fast growing and currently widely applied method in the diversity estimation of aquatic biota; even though morphological identification is still carried out. The molecular approach is beneficial complementing on regular surveys, e.g. use of nets, traps, fishing rods, and even with poisons. In this study, the eDNA metabarcoding was applied to water samples around the Pondok Dadap fish landing station, Indonesia to determine the diversity of fish around the waters and also to identify marine fish landed in this area. Molecular identification was carried out on fish samples obtained from the fish market improved GenBank database on COI and ITS. While, seawater samples were carried out by using the next-generation sequencing (NGS) platform to obtain the eDNA metabarcoding data for the first time. Molecular identification obtained 34 species (68 sequences of COI and ITS regions) belonging to 28 genera, 18 families, 4 orders, while the eDNA metabarcoding approach identified 53 marine fish species by using the MiFish pipeline representing 38 genera, 27 families, and 7 orders. From the present study, we can able to estimated fish diversity by eDNA metabarcoding, and this finding will be helpful for baseline data preparation for future effective management of resources in this area.